Sensitivity study of a locally developed six electrode focused impedance method - Khanal Trilochan; Rabbani K Siddique-e (Journal of Electrical Bioimpedance)
The Focused Impedance Method (FIM) is a new technique of electrical bioimpedance measurements in the human body. The idea originated in Bangladesh and provides an opportunity for localized measurement of bioimpedance down to reasonable depths from the body surface using skin surface electrodes. This has potential applications for physiological studies of targeted organs in the body and in detecting or diagnosing diseases and disorders. FIM is based on the age-old Tetra-Polar Impedance Measurement (TPIM) but provides a few significant improvements.